Real-time detection of damage evolution using electrohydrodynamic printing. (January 2021) - Kim, Keon-Young; Lee, Chang-Yull
Highlights: A new sensing mechanism for real-time monitoring of the structures. Electrohydrodynamic printing for the fabrication of sensors. PZT/PVDF composite inks for stable resistance changes. Real-time detection of both microscopic damages and propagation. Detection of damages through resistance changes. Abstract: The Non-destructive testing methods are important for the detection of material degradation in aerospace structures. However, it is difficult to monitor structural damages caused by aerodynamic loads, shocks and fatigue during the flight of the aircraft in real time. Therefore, conventional non-destructive inspections are usually performed at periodic maintenance checks. This paper proposes a development of a new sensing mechanism for the real-time monitoring of microscopic damage based on electrohydrodynamic (EHD) technology. Piezoelectric grid sensors were made with Ag inks and PZT/PVDF inks. The piezoelectric effect was used to observe and estimate changes in structures. The sensor formed a layered grid structure by printing uniform piezoelectric lines in the horizontal and vertical directions. The manufactured grid sensor can detect the damages of the structure through changes in resistance, and the damaged vicinity was estimated using the intersections of the resistance changes of piezoelectric lines. The proposed mechanism was found to be a powerful methodology for real-time monitoring the microscopic damages and damage evolution of structures.